Pelatihan dan Perbaikan Instalasi Listrik di Taman Gereja bagi Pemuda GMIM Golgota Malendeng - Deitje S. Pongoh; Sukandar Sawidin; Muchdar D Patabo; Arnold R Rondonuwu (JURNAL UMBANUA, 2022)
The youth congregation of the Malendeng church today is always having trouble finding installers to install, repair or develop lighting installations in the church environment because currently the courtyard or garden of the Golgota Malendeng church at night looks dark so that it interferes with activities if there are worship activities at night, especially at night. Christmas, New Year and so on. This Community Service activity will be carried out at the Golgota Malendeng Church Park with the aim of repairing and installing lighting installations and training church youth to become installers who are able to install lighting installations in a church or simple residential area. The method used is to identify problematic electrical installations, make electrical installation plans and conduct simple electrical installation training. The results obtained from this activity can replace and install electrical installations for lighting lamps in the Malendeng Golgotha Church Park. For street lights to the Malendeng Golgotha Church, there are 4 light pole points, 6 light points for the garden and 2 points for the church headlights